Pengaruh Pemberian Air Rebusan Daun Kersen (Muntingia calabura L.) Terhadap Penurunan Kadar Glukosa Darah Pada Mencit Diabetes Melitus - Rivaldi, Rivaldi; Salma, Wa Ode (NHM PRESS, 2024)
Diabetes Mellitus (DM) is a chronic or chronic disease in the form of a metabolic disorder, characterized by high blood sugar levels. So treatment can be done by regularly consuming foods and herbal medicines that contain high levels of antioxidants such as flavonoids, saponins, tannins and alkaloids. Cherry leaves (Muntingia calabura L) are a plant that contains antioxidants. Therefore, this study aims to determine the effect of giving boiled water from cherry leaves (Muntingia calabura L.) on reducing blood glucose levels in mice with diabetes mellitus. This type of research is a pre-experimental laboratory using a pretest and posttest control group research design. A total of 20 mice were selected using a purposive sampling technique which were then divided into 4 groups, namely positive control group, negative control, treatment 1 (young cherry leaves with a dose concentration of 5%) and treatment 2 (young cherry leaves with a dose concentration of 10%). Bivariate analysis was carried out using the ANOVA test with the LSD Post-Hoc follow-up test. The research results obtained showed that giving a decoction of young cherry leaves had a significant effect on reducing blood glucose levels (p<0.05), and there was a significant difference between treatment groups, namely P1 versus P2 (p<0.05). In conclusion, giving a 10% dose of cherry leaf decoction (Muntingia calabura L) was more effective in reducing blood glucose levels in a mouse model of diabetes mellitus.